2019
DOI: 10.1002/cncr.32663
|View full text |Cite
|
Sign up to set email alerts
|

Symptom burden among older breast cancer survivors: The Thinking and Living With Cancer (TLC) study

Abstract: Background Little is known about longitudinal symptom burden, its consequences for well‐being, and whether lifestyle moderates the burden in older survivors. Methods The authors report on 36‐month data from survivors aged ≥60 years with newly diagnosed, nonmetastatic breast cancer and noncancer controls recruited from August 2010 through June 2016. Symptom burden was measured as the sum of self‐reported symptoms/diseases as follows: pain (yes or no), fatigue (on the Functional Assessment of Cancer Therapy [FAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 41 publications
9
55
2
Order By: Relevance
“…Taken overall, the results of this study, when combined with findings from previous reports [ 2 , 10 ], highlight the need for caregivers to emphasize screening for and discussion of symptoms, including sleep difficulties, fatigue, loss of strength, aches and pains, and muscle or joint stiffness. Of particular concern are younger survivors and those who are African American or low-income.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Taken overall, the results of this study, when combined with findings from previous reports [ 2 , 10 ], highlight the need for caregivers to emphasize screening for and discussion of symptoms, including sleep difficulties, fatigue, loss of strength, aches and pains, and muscle or joint stiffness. Of particular concern are younger survivors and those who are African American or low-income.…”
Section: Discussionsupporting
confidence: 71%
“…Important correlates of having reported symptoms included age, race, marital status, and household income. Madelblatt et al [ 10 ] noted that older breast cancer survivors may have a high symptom burden due to comorbidities and aging. However, in the current study, almost all of the symptoms were more likely to be reported by participants who were less than 55 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies were used to develop clinical risk‐prediction models, such as the CARG Chemotherapy Toxicity Score and the Chemotherapy Risk Assessment Scale for High‐Age Patients (CRASH) Score 20,34,35 . Similarly, longitudinal cohort studies can provide important insights into the late‐term effects of cancer treatment on aging in older cancer survivors, as has been done in the Thinking and Living With Cancer (TLC) Study (ClinicalTrials.gov identifier NCT03451383) 80 …”
Section: Discussionmentioning
confidence: 99%
“…Receipt of chemotherapy was an inclusion criterion because these patients are more likely to have residual symptoms and impairments in QOL. 62 , 63 Of the participants who enrolled, there was high retention (84%, n = 27 of 32). Study visit attendance among those retained was nearly 100%, which is an indication of strong adherence and participant engagement throughout the intervention despite the fact that 91% were employed and working at the time of study entry.…”
Section: Discussionmentioning
confidence: 99%